1983
DOI: 10.1002/aic.690290505
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive diffusion in aluminas

Abstract: The effect of the ratio of solute molecular diameter to the substrate pore diameter on the diffusion of polyaromatic compounds in four different pore sizes of amorphous gamma-aluminas was studied at atmospheric pressure and ambient temperature. Diffusion rates of the polyaromatic compounds in the aluminas decreased as the ratio of solute molecular diameter to pore diameter increased. Empirical correlations between the apparent reduction in solute effective diffusivity and the ratio of molecular diameter to por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 20 publications
(22 reference statements)
2
86
0
Order By: Relevance
“…As shown by Massoth and coworkers (Chantong and Massoth, 1983;Tsai et al, 1991), these different empirical or semiempirical expressions are basically the same. Furthermore, hindered diffusion behavior in alumina is different from that in membranes.…”
Section: Do1mentioning
confidence: 81%
See 4 more Smart Citations
“…As shown by Massoth and coworkers (Chantong and Massoth, 1983;Tsai et al, 1991), these different empirical or semiempirical expressions are basically the same. Furthermore, hindered diffusion behavior in alumina is different from that in membranes.…”
Section: Do1mentioning
confidence: 81%
“…Most of the investigators tried to correlate their diffusion data with the theoretical models developed for membranes. Some studies showed that their data could be well represented by the Renkin equation (Chantong and Massoth, 1983;Limbach and Wei, 1990;Tsai et al, 1991;Rhee and Guin, 1994), while others observed the agreement of their results with the Beck and Schultz's power law of different z values ranging from 3.5 to 5.2 (Chantong and Massoth, 1983;Spry and Sawyer, 1975;Cheng et al, 1990;Tsai et al, 1991;Lee et al, 1991;1991a). Guo et al (1990) On the other hand, due to the different pore structures between membranes and porous alumina and silica, some different results have been observed, and different hindered diffusion concepts were proposed.…”
Section: Hindered Diffusion In Alumina Silica and Porous Catalystsmentioning
confidence: 99%
See 3 more Smart Citations